2012
DOI: 10.2147/jbm.s35895
|View full text |Cite
|
Sign up to set email alerts
|

Determination of reference ranges for full blood count parameters in neonatal cord plasma in Hilla, Babil, Iraq

Abstract: BackgroundThe health of an individual is known to vary in different countries, in the same country at different times, and in the same individuals at different ages. This means that the condition of individuals must be related to or compared with reference data. Determination of a reference range for the healthy term newborn is clinically important in terms of various complete blood count parameters. The purpose of this study was to establish a local reference range for full blood count parameters in neonatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
18
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 10 publications
11
18
1
Order By: Relevance
“…The mean reference values for red blood cell count and haemoglobin concentration in neonates in this study were similar to the earlier studies [1,8,9] while lower value of haematocrit observed in this study compared to previously reported values of 44 -48% [1,4,8] may be associated with varying numbers of newborns, time interval between births, ethnic and dietary factors amongst other factors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The mean reference values for red blood cell count and haemoglobin concentration in neonates in this study were similar to the earlier studies [1,8,9] while lower value of haematocrit observed in this study compared to previously reported values of 44 -48% [1,4,8] may be associated with varying numbers of newborns, time interval between births, ethnic and dietary factors amongst other factors.…”
Section: Discussionsupporting
confidence: 91%
“…The importance of determination of haematological reference values for full term healthy neonates cannot be overemphasized as the changes in some of the blood cell parameters are of clinical importance [1,2] .…”
Section: Introductionmentioning
confidence: 99%
“…This study showed no statistically significant decrease in white blood cells (WBCs) and platelets counts in newborns' cord blood sample but showed a mildly statistically significant difference in the reticulocyte count between the group I and group II (vaginal groups; augmented and non-augmented), where the augmented vaginal group showed reticulocyte count higher than spontaneous vaginal group, in the other hand no statistically significant difference was found between vaginal and cesarean section group in reticulocyte count (Table 3) which may explained as that augmented group exposed to more hypoxia and stress due to more contractions. In this study there were no statistically significant differences in hemoglobin level for newborns' cord blood as regard to newborns' sex which agreed with a study reported by Jopling et al, [11] and Jasim et al, [12] but not agreed the results that had been reported by Mamoury et al, [13]. In this study we found positive correlations among newborns' cord blood hemoglobin as regard to head circumference, newborn length, fetal gestational age but we found a negative correlation among newborns of the three studied groups as regard to birth weight (Table 4).…”
Section: Discussionsupporting
confidence: 93%
“…x10 9 /l) (23) and Sagamu Nigeria (4.3 x10 9 /l). On the contrarily, the higher limit of RI of Hgb value (19.6g/dl) of this study was consistent to a study reported in Saudi Arabia (19.7g/dl) (23) but higher than in a study reported in Logas Nigeria (14.8g/dl) (17), Pakistan (17.3g/dl) (25), Iraq (15.22g/dl) (26), and Nepal (17.2g/dl) (18). The difference of Hgb value might be due to method variation, inclusion criteria of the study participants and time of cord clamping.…”
Section: Discussionsupporting
confidence: 92%